PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN GAYA BELAJAR AUDITORIAL TERHADAP HASIL BELAJAR DI SEKOLAH DASAR - Girang Awan Satriyo Aji; Nila Roudlotul Jannah; Dimontiq Salsabila Putri Andy (PROCEEDING UMSURABAYA, 2022)
In this study, the researcher examines the effect of the Problem Based Learning model and the Auditorial Learning Style of students on student learning outcomes in grade IV Elementary School. The method used in this research is an experimental method with a quantitative approach. The independent variables in this study are Problem Based Learning (X1) and Auditory Learning (X2) learning models. The dependent variable in this study is student learning outcomes (Y). The sample population in this study included all fourth grade students at SD Banyu Urip, totaling 34 students. The results in this study indicate that the use of the Problem Based Learning Method has a significant influence in efforts to improve student learning outcomes with an average ratio of 82.44. While student learning styles also affect the increase in the value of student learning outcomes with an average value ratio of 70.4. Judging from the results of this study, it can be concluded that learning by applying the Problem Based Learning Method and Auditory Learning Style has little impact on the high student learning outcomes in learning Natural Sciences and is included in the size criteria in the medium category.Â Keywoard: auditory learning style; learning outcomes; learning model; problem based learning;